A Evaluate the biological activity of Citrullus Colocynthis extract (In vitro study) - YOUSIF, HAYDER; Zahraa F Shaker; Hayder Hamed Abed (Al-Qadisiyah Journal of Pure Science, 2021)
The plant of c. colocynthis is perennial herbal of the Cucurbitaceous types that is used as a traditional medicinal plant on a Mediterranean tub and equatorial nations.Studies on the antibacterial properties of Citrullus colocynthis leaf extract, Medicinal plants have conventional been used in abortifacient and treats constipation, edema, Infection caused by bacteria, cancer and diabetes problems.The antibacterial efficacy of citrullus colocynthesis (L.) was investigated in this work using five species of pathogenic bacteria isolated from urinary tract infections: E. coli, Klebsiella pneumoniae, Streptococcus spp, Psudomonas auroginosa, and Staphylococcus aureus. For the antibacterial test, water and ethanol extract were employed.The ethanolic extract showed inhibitory activity against Escherichia Coli at (100 °C, 80 °C, 60 °C) while Staphylococcus aureus at (100 °C, 80 °C), Streptococcus spp. at (100 °C). Water extract exhibited less or no activity against all types of bacteria.The findings of this investigation indicate that C. colocynthis might be utilized to treat disorders caused by the test organisms.